Dampak Kebijakan HPP dan Perilaku Penjualan terhadap Pendapatan Petani Jagung di Kecamatan Lengkiti Kabupaten OKU - Elmi Amelia; Fifian Permata Sari; Yetty Oktarina (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the HPP policy and sales behavior in relation to the income of corn farmers in Lengkiti Subdistrict, OKU Regency. The method used was a survey employing simple random sampling. The research design was a survey, and the sampling method used was purposive sampling.  The sample was drawn from the two villages with the largest number of corn farmers: Bandar Jaya Village (318 farmers) and Fajar Jaya Village (266 farmers). Using the Slovin formula, a sample size of 85 was determined.  The study was conducted in January 2026. The data obtained were then tabulated and analyzed using an analysis of farmers’ income and sales behavior, while the effect of the Government Purchase Price (HPP) was analyzed using multiple linear regression. The results of the study indicate that the Government Purchase Price (HPP) has a positive and significant partial effect on the income of corn farmers in Lengkiti Subdistrict, OKU Regency. Sales behavior does not have a significant partial effect on the income of corn farmers in Lengkiti Subdistrict, and the government purchase price and sales behavior simultaneously have a significant effect on the income of corn farmers in Lengkiti Subdistrict, OKU Regency.